Pengaruh Edukasi Demonstrasi Terhadap Kemampuan Dalam Melakukan Praktik SADARI pada Siswi SMA PGII 2 Kota Bandung - Sri Iriani,, Oktarina; Sari, Dian Purnama; Rosita; Syafrullah, Haidir; Ardayani, Dini Sandi (Jurnal Ilmu Kesehatan Immanuel, 2024)
Breast cancer is a disease that often occurs in women throughout the world. Early detection has an important role in increasing the cure rate and reducing the death rate due to breast cancer. The breast self-examination method is a simple method that can be used to detect early changes or abnormalities in the breasts. This research aims to investigate the effect of demonstration of breast self-examination called SADARI among female students at PGII 2 Senior High School in Bandung. This research involved 70 female students as research samples. The sample was selected using a simple random sampling technique. This research used a survey method using a checklist as a data collection instrument. The data collected includes information about the practice of SADARI, and the effect of giving a demonstration on the practice of SADARI. This research shows that before giving the demonstration 97.1% of female students did not have the ability to practice SADARI and after being given the demonstration 84.2% had the ability to practice SADARI. The results of statistical tests of ability before and after shows the Asymp.Sig value = 0.000 (<0.05). There is a significant influence on the implementation of the practice of SADARI on increasing the ability of female students in efforts to detect breast cancer early. It is hoped that the school will always carry out socialization about health to female students and collaborate with health workers, especially regarding breast self- examinations by doing SADARI, so that female students can be aware of changes in their bodies and know the importance of practicing breast self-examination regularly to detect possible abnormalities in the breasts, and it could be one of the providing information to the community or closest family about the practice of breast self-examination so that it is hoped that it can reduce the number of breast cancer.Keywords: SADARI, demonstration, Practice